THE DESCRIPTION OF MODIFIABLE RISK FACTORS IN CORONARY HEART DISEASE AT DR. SOETOMO REGIONAL PUBLIC HOSPITAL - Mayla Renata Sandi; Santi Martini; Kurnia Dwi Artanti; Sri Widati (Jurnal Berkala Epidemiologi, 2019)
Background: Coronary heart disease (CHD) is a non-communicable disease that causes the highest mortality in the world, including in Indonesia. Risk factors for CHD are divided into modifiable and non- modifiable risk factors. Purpose: This study aims to discover the description of risk factors that are modifiable in coronary heart disease patients at Dr Soetomo Regional Public Hospital. Methods: It was a descriptive observational study with cross sectional study design. The study population was coronary heart disease patients who were doing outpatient treatment at the Integrated Heart Service Center (PPJT) of Dr. Soetomo Regional Public Hospital. The number of study sample was 72 respondents using accidental sampling technique. Data sources used are primary data using questionnaires and secondary data using medical record. Data were collected during November 2018. The location of this study was Dr. Soetomo Regional Public Hospital. The data analysis technique chosen was univariate analysis and presented in the form of a frequency distribution table. Results: The results of the study showed that the characteristics of respondents were mostly between 56-65 years old (43,05%) and male (70,84%). Risk factors found on the respondents were smoking (84,72%), hypertension (72,22%), hyperlipidemia (68,05%), diabetes mellitus (81,94%) and poor physical activity (77,77%). Conclusion: Modifiable risk factor that was mostly found on coronary heart patients was smoking, while least one was hiperlipidemia.